Full-scale tests of transporting pipeline sections – a review and consequences to our investigations - DAKHEL, AHMAD YASSER; Lukács, János (Design of Machines and Structures, 2023)
Hydrocarbon transport pipelines’ safe operation is an economic and environmental interest. These pipelines are typically designed for static loads, but during their long-time operation – due to pressure changes and environmental impacts – they are also subject to cyclical loads. The individual pipe sections are connected by girth welds, which represent potential sources of hazards in terms of damage. In order to assess the reliability of girth welds, full-scale tests are carried out under simple and complex loads. The purpose of this article is twofold. On the one hand, summarize the full-scale tests on transmission pipelines, with special attention to the tests on girth welds; on the other hand, based on this, draw con-clusions for the design and implementation of our own full-scale tests.